DEVELOPMENT OF A VIRTUAL STORE USING WORDPRESS AND WOOCOMMERCE FOR A MARKETING COMPANY. CASE: PROFESSIONAL NURSING SERVICES - Presenda, Freddy Alberto Morcillo; Ferreira, Arturo Corona; de la Cruz, José Trinidad Acosta; Rodríguez, José Manuel Hernández; Reyna, Manuel Villanueva; Gustavo , Lia; Castañeda, Adolfo Chapus (Seven Editora, 2025)
Adapting to technology is becoming more and more common and important, since nowadays using the Internet is usually an indispensable tool to carry out any activity. Nowadays the Internet is one of the most effective means to offer services to clients, so a web application will be developed using WordPress and WooCommerce to facilitate the hiring of professional services in nursing. DOI: https://doi.org/10.56238/sevened2025.021-082